Dual effects of heme oxygenase-1 on astrocyte injury induced by hemin in vitro. (2nd January 2016) - Chen, Hao; Wang, Xingqi; Zhao, Qiuchen; Zhang, Zuohui; Ye, Xinchun; Hua, Fang; Cui, Guiyun
Abstract: Primary objective : The purpose of this study was to investigate the effects of heme oxygenase-1 (HO-1) on astrocyte injury induced by hemin. Research design : Primary astrocytes were isolated from Sprague Dawley rat pups and cultured in vitro . The expression of HO-1 was induced by hemin in a quantitative fashion and the effects of HO-1 on hemin-induced astrocyte injury were estimated by cell viability, cell membrane permeability and apoptosis. Methods and procedures : Astrocytes were divided into control group, hemin 5 μM group, hemin 5 μM + Zn-PPIX group, hemin 30 μM group and hemin 30 μM + Zn-PPIX group. Survival quality of astrocyte was measured by WST-8 assay, LDH assay, Hoechst 33258 Staining and annexin V-FITC/PI assay and apoptotic-related proteins were measured using Western blotting. Main outcome and results : Hemin could dose-dependently up-regulate the expression of HO-1. HO-1 exerted a protective role on astrocyte damage induced by 5 μM hemin, including increased cell survival rate and anti-apoptotic proteins expression (Bcl-2 and p-AKT), as well as decreased LDH release, apoptosis ratio and apoptotic protein expression (Bax, p-ERK and cleaved-caspase3). However, the effect of HO-1 on astrocyte injury between 30 μM hemin-treated groups was opposite of the protective role in 5 μM hemin-treated groups. Conclusions : There were dual effects of HO-1 in 5 μM and 30 μM hemin-induced astrocyte injuries.